A curious companion for elderly gamers - Wu, Q. (2013)
The rapidly expanding elderly population is a significant niche market for game developers. However, the main target audiences of the existing digital games are young generations, who do not warrant the special needs required by elderly. In this paper, based on the field study of game for elderly - Chinese Water Painting - we propose a curious companion for the elderly. The curious mechanism of the artificial companion is developed based on Berlyne's model of curiosity. The implementation considers three needs of the elderly: the smoothness of game playing, the entertainment, and the caring for the elderly. A preliminary study suggests a wide range acceptance of the curious companion.